Participatory numbers for integrating knowledge and actions in development. Issue 8 (16th November 2016) - Gaillard, J.C.; Cadag, Jake Rom; Gampell, Anthony; Hore, Katherine; Le Dé, Loic; McSherry, Alice
ABSTRACT: This article discusses the opportunities and challenges associated with the use of quantitative participatory methods and participatory numbers for integrating locals' and outsiders' knowledge, as well as actions from the bottom-up and top-down, in development. It places emphasis on the contribution of quantitative participatory methods and participatory numbers to foster dialogue between a wide range of stakeholders, for example, local people, NGOs, government agencies and scientists, who usually seldom directly engage with each other. The article draws on case studies that discuss remittances and disasters in Samoa, and disaster risk reduction in the Philippines.